Theory and conception of Somatopsyche Psychiatric Intervention: a transdiagnostic body-mind intervention for psychiatric practice - Guerra, Renata Fáro; Tavares, Hermano (Frontiers in Psychiatry, 2025)
This article introduces the Somatopsyche Psychiatric Intervention (SPI), a novel body-mind approach that integrates body awareness practices, meditation, and contemporary neuroscience theories in the treatment of psychiatric conditions. SPI is structured in seven steps across eight weekly sessions, aiming to enhance emotional regulation, decision-making, and patient resilience. While the model is still undergoing empirical validation and should be considered primarily theoretical at this stage, it has been implemented biannually in a clinical outpatient setting since 2019. Preliminary data collection using validated instruments (e.g., the MAIA scale) is ongoing and will inform future publications. The SPI represents a promising integrative framework in mental health care, although challenges remain regarding the training of professionals and adaptation by patients used to more traditional methods. Further studies, including pilot trials and comparative analyses, are planned to rigorously evaluate its effectiveness.